Trends and Influential Works in Sustainable Crop Management: A Bibliometric Study - Kunu, Pieter J.; Elizabeth, Roosganda; Sulandjari, Kuswarini; Rukmana, Arief Yanto (West Science Interdisciplinary Studies, 2023)
This bibliometric study examines how the field of sustainable crop management research is developing through an analysis of publications and their citations. We use VOSviewer software and sophisticated bibliometric approaches to find emergent research subjects, co-authorship networks, trends, and influential publications. Our data shows a significant increase in research publications over the course of four decades, which is indicative of the growing understanding of the significance of sustainable agriculture. Key publications by well-known writers offer fundamental information, and co-authorship networks emphasize cooperative research initiatives. Agroecology and climate-resilient agriculture are two emerging study subjects that provide insights into the field's future orientations. Through an awareness of these trends and key publications, this research helps to support well-informed decisions about food security and sustainable agriculture.